2016
DOI: 10.1007/s11356-016-6502-y
|View full text |Cite
|
Sign up to set email alerts
|

USPIO assisting degradation of MXC by host/guest-type immobilized laccase in AOT reverse micelle system

Abstract: The laccase and ultrasmall superparamagnetic iron oxide nanoparticles (USPIO) have been assembled inside the tubular mesoporous silica via co-adsorption technology to prepare host/guest-type immobilized laccase, which is applied to degrade methoxychlor (MXC) in aqueous and reverse micelle environments. The effects of various parameters on degradation of MXC were studied. Under the optimum conditions, the degradation rate could reach maximum value of 45.6 % and remain at 20.8 % after seven cycles. Moreover, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…For the degradation of chlorpyrifos, Nandabalan et al (2017) observed that at a loading rate of 20 mg Lac immobilized on magnetic nanoparticles, the enzyme retained 95% of its activity after five consecutive cycles and degraded 99% of the insecticide within 12 h of incubation at pH 7°C and 60°C. In the case of methoxychlor, Yang et al (2016) reported a degradation rate of methoxychlor of about 46% under optimal conditions with Lac immobilized on tubular mesoporous silica containing ultrasmall superparamagnetic iron oxide nanoparticles as catalyst. The authors observed that the degradation rate was 20.8% after seven cycles.…”
Section: Immobilization Of Wrf Lac On Synthetic Supportsmentioning
confidence: 99%
“…For the degradation of chlorpyrifos, Nandabalan et al (2017) observed that at a loading rate of 20 mg Lac immobilized on magnetic nanoparticles, the enzyme retained 95% of its activity after five consecutive cycles and degraded 99% of the insecticide within 12 h of incubation at pH 7°C and 60°C. In the case of methoxychlor, Yang et al (2016) reported a degradation rate of methoxychlor of about 46% under optimal conditions with Lac immobilized on tubular mesoporous silica containing ultrasmall superparamagnetic iron oxide nanoparticles as catalyst. The authors observed that the degradation rate was 20.8% after seven cycles.…”
Section: Immobilization Of Wrf Lac On Synthetic Supportsmentioning
confidence: 99%